PSO-Aided Inverse Design of Silicon Modulator - Zijian Zhu; Yingxuan Zhao; Zhen Sheng; Fuwan Gan (IEEE Photonics Journal)
Optimizing doping profiles has always been a key approach to enhance the performance of silicon modulators. Nevertheless, the pursuit of innovative profiles has encountered barriers in recent times. To tackle this issue, the idea of inverse design, widely adopted in passive photonic devices, can be employed in silicon active devices. As a result, we incorporate the inverse design method with the particle swarm optimization (PSO) algorithm and achieve a G-shaped doping profile for the modulator, exhibiting superior $V_{π } L$ of 0.68 V $·$ cm and low loss of 9.3 dB/cm. The small-signal frequency response suggests a reliable operation range under reverse biases of 1 $\sim$ 3 V with the bandwidth over 26 GHz. The silicon modulator with a G-shaped design demonstrates remarkable efficiency in modulation and very low loss, suggesting its great potential for application in microwave front-end systems. The use of inverse design shows great potential in enhancing active silicon photonic devices, allowing for faster, higher-capacity, and more reliable data communication systems.